PELATIHAN PENGINPUTAN DATA SECARA OTOMATIS DI MICROSOFT EXCEL MENGGUNAKAN DATA FORM DAN MACRO VBA (BASIC FOR APLICATION) DI SMA IT UNGGUL AL-MUNADI MEDAN - Siregar, Elida Tuti; Alfina, Ommi; Puspita, Dahlia; Safii, M. (Universitas Methodist Indonesia, 2023)
Automatic data input using Microsoft Excel as a number processor or application for automatically processing data such as numerical values, mathematical formulas and making financial reports hone students' skills in knowledge of the use of computer technology, which is a basic need nowadays to operate a computer, a skill that students must master in the future world of work. because computer operating skills are really needed by companies, especially the Microsoft Excel application to process technology-based company data in determining decision makers in a company. This training will produce graduates who can operate computers and input data automatically. This activity provides skills and knowledge to students at SMA IT Unggul Al Munadi Medan using Microsoft Excel to process and input data automatically with Visual Basic forms and macros (VBA)